Independent strong domination in complementary prisms - Zeynep Nihan Berberler; Murat Ersen Berberler (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2020)
Let G = (V, E) be a graph and u,v ∈ V. Then, u strongly dominates v if (i) uv ∈ E and (ii) deg(u) ≥ deg(v). A set D ⊂ V is a strong-dominating set of G if every vertex in V-D is strongly dominated by at least one vertex in D. A set D ⊆ V is an independent set if no two vertices of D are adjacent. The independent strong domination number is(G) of a graph G is the minimum cardinality of a strong dominating set which is independent. Let Ġ be the complement of a graph G. The complementary prism GĠ of G is the graph formed from the disjoint union of G and Ġ by adding the edges of a perfect matching between the corresponding vertices of G and Ġ. In this paper, we consider the independent strong domination in complementary prisms, characterize the complementary prisms with small independent strong domination numbers, and investigate the relationship between independent strong domination number and the distance-based parameters.